Teddy bear,teddy bear, go out to play - Krutop, Lee (Brimax Publishing Victoria, Australia, 2007)
This classic nursery rhyme, brought to life through engaging illustrations, provides a soothing and rhythmic reading experience for young children. It encourages language development, memory recall, and imaginative play.